2017
DOI: 10.1248/cpb.c16-00925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Heterocyclic Compounds Incorporate 4,5,6,7-Tetrahydrobenzo[<i>b</i>]thiophene Together with Their Cytotoxic Evaluations

Abstract: The 2-amino-3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophene was the key starting compound used to synthesize new thiazole, pyrimidine, pyran, pyridine and thiazine derivatives. The cytotoxicity of the synthesized compounds was studied towards the three cancer cell lines namely MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and SF-268 (central nervous system (CNS) cancer) in addition to the normal cell line (WI-38) using doxorubicin as the reference drug. The study showed that compounds 5, 9a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In continuation of our previous work, [31][32][33][34][35][36][37][38] the current study reported synthesizing some novel thiazole de- rivatives based on 4-phenylthiazol-2-amine. The anticancer activity for all the synthesized compounds was evaluated.…”
Section: Introductionmentioning
confidence: 68%
“…In continuation of our previous work, [31][32][33][34][35][36][37][38] the current study reported synthesizing some novel thiazole de- rivatives based on 4-phenylthiazol-2-amine. The anticancer activity for all the synthesized compounds was evaluated.…”
Section: Introductionmentioning
confidence: 68%
“…The reaction of dimedone (1) with any of the aromatic aldehydes 2a-c gave the benzylidene derivatives 3a-c, respectively. Compounds 3a-c were appropriate for Gewald's thiophene synthesis [24][25][26] through the reaction of any of compounds 3a-c with either of malononitrile (4a) or ethyl cyanoacetate (4b) and elemental sulfur gave the 6,7-dihydrobenzo[b]thiophen-5(4H)-one derivatives 5a-f, respectively. The structures of compounds 5a-f were based on their analytical and spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…In the current work, we are explaining the synthesis of thiazole derivatives together with their antitumor evaluation, in proceedings to our concern in synthesize of bioactive heterocyclic compounds. Thus, compound ( 1 ) 2‐(4‐oxo‐4,5‐dihydrothiazol‐2‐yl)acetonitrile, which was obtained as reported in literature by the reaction of malononitrile with thioglycolloic acid in acetic acid solution, reacted with any of acetphenone, 4‐chloroacetophenone, or 4‐methylacetophenone in an oil bath at 120°C to afford the respective compounds 2a‐c through the Knoevenagel reaction (Scheme ).…”
Section: Resultsmentioning
confidence: 99%